Pakistan Army Green Book 1990 : Year of the Junior Leaders 1990 - Pakistan Army; Editorial Board : Brig. Muhammad Jamil Qudrat Warsi; Lt. Col. Muhammad Shabraz Abbasi and Lt. Col. Syed Ishfaq Ali (GHQ, Rawalpindi Pakistan Army, 1990)
The views expressed in this book are those of the authors and not to be taken as the official opinion or policies of the General Headquarters.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals